Diagnostic accuracy of rapid immunochromatographic test compared to ELISA in dengue fever - P. S., Pooja; Kokate, Sandeep B.; Shrikhande, Sunanda (International Journal of Research in Medical Sciences, 2025)
Background: Dengue fever is a significant mosquito-borne viral disease affecting tropical and subtropical regions. Early and accurate diagnosis is vital for patient care and outbreak control. While enzyme-linked immunosorbent assay (ELISA) is considered the reference standard for dengue diagnosis, rapid immunochromatographic tests (ICTs) offer quicker, simpler alternatives suitable for point-of-care settings. Methods: This cross-sectional study evaluated 429 clinically suspected dengue cases from July 2022 to June 2024. Serum samples were tested for NS1 antigen, IgM, and IgG antibodies using both rapid ICTs and ELISA. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated using ELISA as the gold standard. Results: The sensitivity of ICTs for NS1 antigen, IgM, and IgG antibodies was 70.97%, 67.14%, and 68.18%, respectively. The corresponding specificities were 99.50%, 99.44%, and 99.51%. PPVs exceeded 97% for all markers, while NPVs ranged from 89.88% to 90.96%. Conclusions: Rapid ICTs demonstrate high specificity but moderate sensitivity, supporting their use as initial screening tools. ELISA remains essential for confirmatory diagnosis, especially in cases of strong clinical suspicion.